2005
DOI: 10.1158/1078-0432.ccr-05-0547
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A8 Is Up-Regulated During Mouse Mammary Gland Involution and Predicts Poor Survival in Breast Cancer

Abstract: Purpose: Microarray studies have linked Annexin A8 RNA expression to a ''basal cell^like'' subset of breast cancers, including BRCA1-related cancers, that are characterized by cytokeratin 5 (CK5) and CK17 expression and show poor prognosis. We assessed Annexin A8's contribution to the overall prognosis and its expression in normal, benign, and cancerous tissue and addressed Annexin A8's physiologic role in the mammary gland. Experimental Design: Using microarrays and reverse transcription-PCR, the Annexin A8 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…This hypothesis is supported by strong evidence from the analysis of gene expression in yeast and emerging data in mammalian cells (23). The h4 signature (Table 3), as well as the h4-related gene list (Supplementary Table S1), includes known markers of basal-like breast cancers, such as K5 and K14 (38), Sox9 (19), P-cadherin (39), laminin (40), fascin (40), epidermal growth factor receptor (41), and Annexin A8 (42), and genes that are expressed primarily in basal myoepithelial cells of the mammary gland, such as WT-1 (43) and S100A2 (Table 3; Supplementary Table S1; ref. 44).…”
Section: Discussionmentioning
confidence: 77%
“…This hypothesis is supported by strong evidence from the analysis of gene expression in yeast and emerging data in mammalian cells (23). The h4 signature (Table 3), as well as the h4-related gene list (Supplementary Table S1), includes known markers of basal-like breast cancers, such as K5 and K14 (38), Sox9 (19), P-cadherin (39), laminin (40), fascin (40), epidermal growth factor receptor (41), and Annexin A8 (42), and genes that are expressed primarily in basal myoepithelial cells of the mammary gland, such as WT-1 (43) and S100A2 (Table 3; Supplementary Table S1; ref. 44).…”
Section: Discussionmentioning
confidence: 77%
“…8 ANX expression has been correlated with patient survival and tumor stage. 8,12,13 Therefore, human ANXs can exhibit oncogenic and/or tumor-suppressing activities, depending on the cell context. In previous studies, we have shown that ANXA10 is a protein specifically expressed in the gastric mucosa, the Brunner gland of the duodenum and the urothelium.…”
mentioning
confidence: 99%
“…In humans, Annexin A8 co-expresses with CK5 and CK17 in a basal cell-like subset of human breast carcinoma with poor survival. Moreover, 85.7% of BRCA1-related breast tumors co-expressed Annexin A8 and CK5 (46). Interestingly, our results indicate a putative association of Annexin A8-like 2 with ovarian tumor progression in BRCA1 carriers.…”
Section: Discussionmentioning
confidence: 59%
“…These peptides share a common structural domain, the annexin core, which consists of 4 or more copies of annexin repeats, responsible for their calcium-regulated membrane-binding activity (46). Annexin A8 was shown to display phospholipid-and F-actin-binding properties, suggesting its involvement in the structural organization of actin-associated membrane domains (47).…”
Section: Discussionmentioning
confidence: 99%